2020 News & Views, April 2001: Global warming changes the forecast for agriculture (Featured article) - International Food Policy Research Institute (International Food Policy Research Institute, 2001)
The latest predictions show that the earth's climate is changing faster than previously thought. How can agriculture remain productive in a warmer world while doing its part to slow climate change?